JUSTIFICATION OF TECHNOLOGY FOR CONDUCTING THERMOMETRIC STUDIES OF GAS WELLS - Mukhammadiyev, Khamidullo (Innovatsion texnologiyalar, 2024)
Increasing hydrocarbon productivity through the rational use of gas and gas condensate fields is becoming urgent. By conducting a thermometric study on gas wells based on the obtained data on temperature distribution, it will be possible to solve such problems as identifying gas recovery intervals from formations, assessing gas recovery from individual formations, determining the conditions for the release of heavy hydrocarbons, and determining the location of a gas flow leak due to a defective pipe connection. Preparation for thermometric studies and their implementation are similar to the biometric method in many ways. Therefore, when applying the thermometry method, it is important to accurately know the technological parameters of wells. At gas wells, this study is carried out using a TEG-36 thermometer. Interpreting the results in shut-in and operating gas wells, it is possible to determine the temperature distribution along the well wall, the stabilization process in various modes, gas recovery intervals and the productivity of individual formations. A deep thermometer device should be lowered directly into gas wells to justify the technology for conducting thermometric research. By processing the results obtained, it will be possible to find a practical solution to problems in the well.